Ewolucja odpowiedzialności nieletnich na przestrzeni lat: brak - Jurgielewicz-Delegacz, Emilia (Studia Prawnoustrojowe, 2019)
This article describes the evolution of juvenile responsibility based on Polish legal regulations developed after Poland regained its independence. For this reason, the description is based on legal acts adopted after 1918. The article deals with such issues as the age of a juvenile, a juvenile’s liability for acts prohibited by law, the consequences of juvenile delinquency. The analysed legal acts include penal codes from 1932, 1969 and 1997 and the act of 1982 on proceedings in juvenile cases.